Perception of Space in the Context of Model Visions of Sustainable Urban Development: Evidence from Warsaw - Thel, Karolina (European Spatial Research and Policy, 2025)
In the presented article, the perception of urban space in the context of the concept of sustainable development (SD) is being addressed. It can be seen as an umbrella term encompassing various model visions of urban development, including green city, creative city, smart city, 15-minute city, just city, participatory city, happy city, inclusive city, and compact city. Based on qualitative research conducted in Warsaw, Poland, key narrative fields for each model have been identified. The article shows how the different model visions are revealed in the expectations and assessments formulated towards urban space. The key conclusions concern the need to change the dominant “flat” narrative of urban sustainability, which is accompanied by a relatively poor language and a one-dimensional view of complex multi-layered issues. The conclusion emphasizes the need to appeal more to the values that are the pillars of the individual model visions of urban SD, as well as issues that appeal to emotions.